Impact and Legal Protection for Concurrent Creditors Due to the Rejection of Homologation of Peace Agreement by Commercial Court - Andinda, Chica Octa; Adam, Richard C. (UNES Law Review, 2023)
This study examines the legal implications and obstacles that arise in the context of bankruptcy and the postponement of debt payment obligations, particularly concerning the settlement agreement between debtors and creditors. The primary focus is on the consequences of the rejection of the homologation of a settlement agreement, wherein the debtor is subsequently declared bankrupt and prohibited from seeking further attempts at reconciliation, in accordance with Article 175 paragraph (1) of the Indonesian Bankruptcy Law (UUK-PKPU).The research delves into the practical implications of bankruptcy, where the curator is responsible for managing the debtor's assets and distributing them to creditors. Concurrent creditors, despite having priority in the distribution of assets, may face the risk of losses if the assets are insufficient to cover the entire debt.Furthermore, obstacles to legal protection for concurrent creditors are also discussed, including bad faith in settlement agreements, such as collusion between debtors and creditors. The condition where the debtor's assets exceed the agreed-upon value in the settlement agreement is also a concern, with the court playing a role in ensuring a fair distribution of assets.By exploring these various aspects, this paper provides a comprehensive overview of the complex dynamics involved in situations of bankruptcy and the postponement of debt payment obligations. It offers insights into the key roles played by the court, creditors, and debtors in the relevant legal context.